2006
DOI: 10.1007/s11373-006-9097-3
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of transneuronal traffic in Streptozotocin-induced diabetes, a WGA-HRP neurohistochemical study in the rat

Abstract: Retrograde transport of Wheat germ agglutinin conjugated to Horseradish peroxidase (WGA-HRP) was used in labeling vagal neurons projecting to the stomach from the dorsal motor nucleus of the vagus nerve (DMNV) in Streptozotocin (STZ)-induced diabetic rats. Diabetes was induced in the experimental rats by intraperitoneal injection of buffered STZ. Control rats were injected with an equivalent volume of the citrate buffer not containing STZ.The experimental rats, which became diabetic about 24 h after intraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Since both groups of rats i.e., diabetic and non-diabetic were subjection to the same experimental procedures it appears logical to attribute the difference in the results of the present study to the diabetic state of the experimental rats. The result of the present study is also consistent with earlier reports in which depletion of labeled vagal neurons were observed following tracer injections of vagally innervated organs of diabetic rats [11,31] . The result of the present study is also in agreement with that of Hellweg et al and Lee et al [5] .…”
Section: Discussionsupporting
confidence: 93%
“…Since both groups of rats i.e., diabetic and non-diabetic were subjection to the same experimental procedures it appears logical to attribute the difference in the results of the present study to the diabetic state of the experimental rats. The result of the present study is also consistent with earlier reports in which depletion of labeled vagal neurons were observed following tracer injections of vagally innervated organs of diabetic rats [11,31] . The result of the present study is also in agreement with that of Hellweg et al and Lee et al [5] .…”
Section: Discussionsupporting
confidence: 93%
“…Streptozotocininduced diabetes in rats has been shown to alter the neurotrophin content in the cervical vagus nerve [22]. In this issue, based on a decrease in the number of retrogradely labeled neurons within the dorsal motor nucleus of the vagus nerve in Streptozotocin-induced diabetic rats as compared with control euglycaemic rats, it was suggested that the retrograde transport process along the axons of the affected neurons was impaired during chronic diabetes [23]. Although impaired neuronal transport is implicated in the findings of Odekunle [23], further investigation is needed to elucidate whether endogenous neurotrophin is involved in the process.…”
Section: Potent Inhibition Of Human Telomerase By U-73122mentioning
confidence: 99%